1978
DOI: 10.1037/h0077494
|View full text |Cite
|
Sign up to set email alerts
|

Burying as a defensive response in rats.

Abstract: In typical laboratory settings, the defensive reactions of animals appear to be limited tofreezing, fleeing, and attacking. However, in the present investigations, rats.tested in the presence of movable ma-> terial incorporated it into a striking and adaptive behavioural sequence. Rats shocked once through a stationary prod buried this shock ^source, even when the shocks-test interval was 20 days. This burying behaviour occurred at a variety of shock intensities and seemed to be controlled sp cifically by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
187
2
2

Year Published

1979
1979
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(207 citation statements)
references
References 36 publications
14
187
2
2
Order By: Relevance
“…In addition to the autonomic changes, behavioral observations show that locomotion and rearing are decreased in KO mice, whereas behaviors reflecting increased conflict, i.e., burying behavior (Pinel and Treit 1978) and stretched approach postures (Rodgers and Johnson 1995) were increased in KO mice. Together with the observed tachycardia and hyperthermia, the increased burying and stretched approach postures are indicative for an enhanced fear/anxiety response in KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the autonomic changes, behavioral observations show that locomotion and rearing are decreased in KO mice, whereas behaviors reflecting increased conflict, i.e., burying behavior (Pinel and Treit 1978) and stretched approach postures (Rodgers and Johnson 1995) were increased in KO mice. Together with the observed tachycardia and hyperthermia, the increased burying and stretched approach postures are indicative for an enhanced fear/anxiety response in KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this test, rats shocked from a stationary, electrified probe push bedding material from the floor of the experimental chamber toward the shock-probe (ie they bury the probe), avoid further contacts with the probe, and exhibit freezing behavior (Treit et al, 1994(Treit et al, , 1981Frye and Seliga, 2003;Pinel and Treit, 1978). In rats it has been demonstrated that anxiolytic drugs such as diazepam decrease burying towards the shock-probe (de Boer et al, 1990;Treit et al, 1993;Tsuda et al, 1988), whereas anxiogenic drugs such as yohimbine increase shock-probe burying (Tsuda et al, 1988).…”
Section: Shock-probe Burying Testmentioning
confidence: 99%
“…Stress reactivity was measured using the shock-probe defensive burying test (Pinel and Treit, 1978) in which the primary index of stress or anxiety is the duration spent by rats burying an electrified probe, with increased burying time providing a measure of elevated stress reactivity or anxiety. Clinically effective anxiolytic agents such as diazepam, chlordiazepoxide, and buspirone attenuate levels of defensive burying (De Boer and Koolhaas, 2003), suggesting that this test is a useful tool for evaluating the anxiolytic potential of novel agents.…”
Section: Introductionmentioning
confidence: 99%